Structural and morphological features of microcrystalline сellulose from soybean straw by organosolvent treatment - T. V. Tkachenko; D. S. Kamenskyh; Y. V. Sheludko; V. O. Yevdokymenko (Хімія, фізика та технологія поверхні)
The main idea of this work is to study the possibility of obtaining microcrystalline cellulose from multi-ton and low-value agricultural waste and investigation its structural properties. Air-dry soybean straw, an agricultural waste, was used for the research. Microcrystalline cellulose (MCC) was obtained from it by the method of organo-solvent cooking. Using the methods of XRD, XRF, FTIR-ATR, AFM, TGA and DSC, the structure and morphology of MCC were studied. It is found that increasing the hydromodule reduces the content of lignin and inorganic components. At the same time, both the yields of the MCC and its qualitative characteristics are declining. First of all, the crystallinity index of the MCC decreases with the increasing amount of the liquor ration. The band corresponded to symmetric CH2 bendings at 1435–1429 cm–1, that is known as the crystallinity band, decreased with increasing amount of the liquor ration. The AFM method shows that when forming the surfaces of MCC 10 particles, not only groups of particles are formed, the heights of the elements of which range from 23.8–28.1 to 16.9–26.8 nm, but also elongated units on the surface of which there are individual particles. The surface roughness is 1.6 nm. At the same time, the surface of the MCC 15 has a surface roughness Ra = 3.1 nm. The particles are distributed throughout the scan, with no clusters of particles and their agglomerates, and their heights are 14.4; 18.7; 20.6; 17.4 and 23.9; 18.1; 24.7 nm. 3D image of the particles showed that the particles are pyramids of different configurations similar to the particles in the MCC 10. It should be noted that the range of depressions and heights characteristic of MCC 15 is much smaller (from –13 to +20.7 nm) than in the MCC 10 (from –17.5 to 45.5 nm).